PESONA: Strategi Promosi Efektif secara Online untuk Niaga dan Pariwisata - Fathurrahman, Akhwal; Fitriana, Ana; Ramadhianti, Risa; Rivaldo, Karis; Septiarni, Marsa; Rizal, Fakhri (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
Digital changes in marketing have created new opportunities for local businesses in villages to reach a wider market. Digital marketing is not only a promotional tool but also an effective strategy to increase the competitiveness of local products in the era of globalization. This research aims to increase the promotion of local products and village tourism by utilizing digital marketing, especially through social media. The method used is a qualitative participatory approach, where village communities are involved in training in content creation and social media account management. The research results show that the implementation of digital marketing strategies has succeeded in increasing public awareness of local products and village tourism, which is reflected in increased sales and tourist visits. This research also emphasizes the importance of branding through product labels to maintain consumer image and trust and increase consumer attraction to local products. Thus, this digital marketing strategy not only contributes to increasing sales and tourist visits, but also plays a role in supporting village economic growth.